The Intergenerational Effect of Maternal Multicultural Experience on Children's Tolerance: An Example From Palestinians and Jews in Israel. (October 2017) - Tadmor, Carmit T.; Berger, Rony; Brenick, Alaina; Abu-Raiya, Hisham; Benatov, Joy
Although recent research has demonstrated the benefits of multicultural experience for reducing personal levels of intergroup bias, the potential for an intergenerational effect has yet to be explored. Using samples of Jewish-Israeli (Study 1a) and Palestinian-Israeli (Study 1b) mother–child dyads, we found that maternal multicultural experience was indirectly related to greater social tolerance among children via lower levels of maternal need for cognitive closure which, in turn, triggered higher levels of maternal social tolerance. These results show that when it comes to multicultural experience, its impact can extend beyond the self to also affect the next generation. Implications for developmental theories of prejudice acquisition and prejudice interventions are discussed.